Natural Sulfur Purification and Its Characterization for Lithium-Sulfur Battery - Haq, Syifa Arinal; Maulana, Fariz Pramudia; Hidayat, Sahrul (Universitas Padjadjaran, 2025)
Sulfur has great potential as a battery cathode material due to its high energy storage capacity. However, contaminants in natural sulfur can negatively impact battery performance and stability. This study aims to enhance the purity and crystallinity of natural sulfur from Kawah Ijen and Tangkuban Perahu using the dissolution-recrystallization method with toluene solvent at 100°C. By dissolving sulfur in toluene, impurities are separated, allowing pure sulfur to recrystallize. XRD analysis revealed that sulfur from Tangkuban Perahu exhibits a higher degree of crystallinity (88,4%) compared to sulfur from Kawah Ijen (75,620%). However, SEM-EDS results showed that sulfur from Kawah Ijen has higher elemental purity, with sulfur content of 91,159% and carbon content at 8,841%. These findings demonstrate that the dissolution-recrystallization method yields different results for sulfur from Tangkuban Perahu and Kawah Ijen. SEM-EDS is effective in measuring chemical purity, while XRD provides insights into the crystal structure. This comparative study highlights the significance of evaluating sulfur from different natural sources, revealing that the higher purity of Kawah Ijen sulfur makes it more suitable for Li-S battery applications. These results have significant implications for local sulfur processing industries, emphasizing the importance of purification techniques in producing high-quality sulfur for advanced Li-S batteries.keywords: sulfur purification, dissolution-recrystallization, Li-S battery, sulfur purity, crystallinity